Pengaruh Strategi Kinerja Karyawan Melalui Analisis SWOT terhadap Produktivitas PT Varuna Tirta Prakasya (Persero) Cabang Surabaya - Fengky Suhendra; Devangga Pratama; Syamsul Arifin (Penerbit Jurnal Indonesia, 2025)
This study aims to describe the employee performance strategy through SWOT analysis on productivity at PT Varuna Tirta Prakasya (Persero) Surabaya Branch. The data analyzed in this study is primary data obtained through questionnaires related to the employee performance strategy through SWOT analysis at PT Varuna Tirta Prakasya (Persero) Surabaya Branch. The data analysis techniques used in this study include descriptive analysis, validity and reliability testing using Pearson’s correlation and Cronbach’s Alpha, as well as path analysis to examine the relationships between the research variables. The research model was tested using Structural Equation Modeling (SEM) with the SmartPLS approach to analyze the relationship between employee performance strategy, SWOT analysis, and employee productivity. The results of the test indicate that employee performance strategy has a significant impact on productivity, while the mediation role of SWOT is less significant. The results of the study show that the employee performance strategy has a significant positive effect on productivity directly. This is indicated by a T- statistic value of 2.829 with a p-value of 0.005, which is smaller than 0.05, demonstrating that the implementation of the employee performance strategy positively contributes to improving the company's productivity. On the other hand, although SWOT analysis acts as a mediator between employee performance strategy and productivity, the direct impact of SWOT on productivity is not significant (p-value of 0.413). This shows that while SWOT analysis can provide valuable insights into internal and external factors, more direct factors, such as improving HR performance, operational innovation, and work processes, have a greater impact on productivity.